Improving access to clinical guidance: redevelopment of a junior doctor intranet page. Issue 1 (30th October 2015) - Walkden, Graham; Millwood, Sinead; Cavanagh, Andrew
Abstract: Junior doctors frequently rely on electronic access to clinical guidelines to inform assessment and management, particularly whilst on-call and occasionally during emergencies. Difficulties in locating and accessing up to date guidance from different hospital intranet sites can lead to delays or errors in patient management. We used a focus group and email feedback to redesign an intranet site for junior doctors which logically organised the documents which doctors said they needed access to in one readily accessible location. A quality improvement project was carried out over six months, testing two iterations of the new junior doctors' intranet site before a third version was launched and evaluated. Their performance was measured by the number of mouse clicks and the time required for doctors to find a representative subset of five guidelines, and revisions were made at each cycle based on feedback from doctors and stakeholders. Cumulatively, we demonstrated a decrease in the total number of clicks required to access the sample of guidelines from 18 to 12 clicks, a corresponding decrease in the time required to access the sample of guidelines from 130 seconds to 22 seconds, and an increase in user satisfaction. We maintained one-click access to emergency guidance. In conclusion, we have developed and implemented an electronic resource for junior doctors which provides more immediate access to both emergency and non-emergency clinical guidance. To ensure the resource remains up to date, it will be maintained by Foundation Programme representatives at our hospital on a rolling basis.